Analisis Sistem Pengendalian Internal Persediaan Gas LPG 3 Kg Pada PT. Restu Inanta - Utami, Yuni; Rozi, Facrul; Nasution, Ilham Ramadhan (Worksheet : Jurnal Akuntansi, 2023)
This research was conducted at PT Restu Inanta, Medan City. This research aims to: find out the internal inventory control system, find out how the system is implemented and the authority and implementation of tasks, and to find out how work practices are implemented at PT Restu Inanta. The data collection techniques used were interviews and observation. The type of research used is qualitative research regarding data collected and expressed in the form of words and images. The research results show that the internal control system for inventory at PT Restu Inanta is not effective and adequate based on an effective and adequate internal control system according to Mulyadi's theory. This is because there are still multiple tasks, in implementing healthy practices in sales and delivery there are no documents with serial numbers printed permanently which can cause negligence in recording.).Keywords: Internal Control System, Inventory